Prediction of in vivo performance of ibuprofen immediate-release products using different dissolution models - Fatma Abdelfattah, Nesrin Taha, Aya Abdou, Nadia Mursi, Laila Emara (Journal of Applied Pharmaceutical Science, 2022)
This study explored the role of different compendial dissolution apparatuses in predicting the pharmacokinetic performance of ibuprofen (IBU) immediate-release (IR) commercial products. Dissolution studies of 200 mg IBU IR tablets of Brufen® (Abbott, Egypt), Nurofen® (Reckitt Benckiser Healthcare, Belgium), and Advil® (Pfizer, USA) were carried out employing the United States Pharmacopeia (USP) I, II, and IV models. Comparison of dissolution profiles was carried out using fit factors, mean dissolution time, and dissolution efficiency. Prediction of in vivo plasma concentration–time profile from in vitro data was carried out by back-calculation of the Wagner–Nelson approach. In vitro/in vivo correlation (IVIVC) was verified between the predicted and actual pharmacokinetic parameters with an estimation of prediction error (PE%). USP II and IV met the accepted dissolution criterion (80% of the label dissolved in 60 minutes) for all IBU IR products, while USP I failed. All commercial tablets showed dissimilar dissolution profiles in all studied models, except Advil versus Nurofen in USP IV. The best IVIVC (R2 values ≥ 0.99 and intercept values close to zero) were observed for Advil in USP II and IV as well as Brufen and Nurofen in USP IV. Accepted PE% values in terms of Cmax and AUCs were achieved for all products in USP IV. The USP IV dissolution model was utilized as a predictive tool for in vivo performances of IBU IR products especially during early product development and, hence, might be adopted as a surrogate for conducting clinical bioequivalence studies.
Keywords: IVIVC, ibuprofen, Wagner– Nelson deconvolution, USP compendial models, flowthrough cell